2019
DOI: 10.2220/biomedres.40.169
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibitors diminish PDGF-BB-induced migration of osteoblasts via suppression of p44/p42 MAP kinase

Abstract: Migration of osteoblasts to the sites resorbed by osteoclasts is an essential step in bone remodeling. However, the exact mechanism of osteoblast migration is still not known. We have shown that platelet-derived growth factor (PDGF)-BB induces the migration of osteoblast-like MC3T3-E1 cells through the activation of p38 mitogen-activated protein (MAP) kinase, c-Jun N-terminal kinase (JNK) and p44/p42 MAP kinase. Evidence is accumulating that heat shock protein 90 (HSP90) acts as a central regulator of proteost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…in particular, JnK activity is required for the initiation of early osteogenic differentiation in mesenchymal stem cells (MScs) (31,32). By contrast, attenuation of JnK activity using JnK inhibitors was found to result in increased late stage osteogenic differentiation (33). These findings suggest that the MaPK/JnK signaling pathway serves a vital role throughout different stages of osteogenic differentiation.…”
Section: Role Of Mapk/jnk Signaling Pathway On the Regulation Of Biolmentioning
confidence: 83%
“…in particular, JnK activity is required for the initiation of early osteogenic differentiation in mesenchymal stem cells (MScs) (31,32). By contrast, attenuation of JnK activity using JnK inhibitors was found to result in increased late stage osteogenic differentiation (33). These findings suggest that the MaPK/JnK signaling pathway serves a vital role throughout different stages of osteogenic differentiation.…”
Section: Role Of Mapk/jnk Signaling Pathway On the Regulation Of Biolmentioning
confidence: 83%
“…7,8,23–25 Additionally, PDGF is a key factor in angiogenesis, which stimulates the migration of various types of cells, including RPE cells. 2628 PDGF signaling has been reported to be enhanced in diabetes. 29,30 Here we used both high glucose and PDGF to induce RPE cell dysfunction and found that both induced EMT and migration of RPE cells following SIRT3 knockdown.…”
Section: Discussionmentioning
confidence: 99%